August's child is … favoured by fortune. Issue 3 (20th June 2013) - Brewer, Lauren M.; Cochran, James J.
<x xml:space="preserve">Abstract</x> Our last issue1 told how some children born under Sagittarius are denied childcare. Here Lauren M. Brewer and James J. Cochran tell how the disadvantage of birth‐month can pursue a child through later education – and through life.